2018
DOI: 10.1177/1744806918782323
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nav1.7 expression in the dorsal root ganglion contributes to pain hypersensitivity after plantar incision in rats

Abstract: Postoperative pain remains a complex problem that is difficult to manage in the clinical context, seriously affecting rehabilitation and the quality of life of patients after surgery. Nociceptors, of which the cell bodies are located in the dorsal root ganglion, are crucial for initiating and conducting the pain signal. The peripheral voltage-gated sodium channels, including Nav1.7, which is mainly expressed in the dorsal root ganglion, are key to understanding the mechanism underlying postoperative pain. Nav1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Studies have shown that deficits in expression and/or function of Nav1.7 may have analgesic effects: Nav1.7 conditional knockout and Nav1.7 blocker protoxin II modulated pain in burn injury models; inhibition of NaV1.7 was effective in treating inflammatory and neuropathic pain in mice . By contrast, the enhancement of Nav1.7 function leads to pain: Enhanced expression of Nav1.7 in L4‐L6 DRGs contributed to pain hypersensitivity after plantar incision; prostaglandin E2 induced up‐regulation of Nav1.7 that was involved in inflammatory pain in rats …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that deficits in expression and/or function of Nav1.7 may have analgesic effects: Nav1.7 conditional knockout and Nav1.7 blocker protoxin II modulated pain in burn injury models; inhibition of NaV1.7 was effective in treating inflammatory and neuropathic pain in mice . By contrast, the enhancement of Nav1.7 function leads to pain: Enhanced expression of Nav1.7 in L4‐L6 DRGs contributed to pain hypersensitivity after plantar incision; prostaglandin E2 induced up‐regulation of Nav1.7 that was involved in inflammatory pain in rats …”
Section: Discussionmentioning
confidence: 99%
“…The schematic drawing shows the central neurite of a primary order dorsal root ganglion neuron and a synapse of such a neuron with a second‐order neuron in the dorsal horn of the spinal cord. The scheme summarises alterations of the voltage‐gated sodium channels (Na V , orange), the adenosine triphosphate (ATP)‐dependent activity of the sodium‐potassium adenosine triphosphatase (Na + /K + ATPase, red), the N ‐methyl‐D‐aspartate receptor (NMDAR, green), the sodium‐potassium‐chloride cotransporter 1 (NKCC1, light blue) the auxiliary voltage‐gated channel subunit α2δ‐1 (purple) and the potassium‐chloride cotransporter 2 (KCC2, dark blue) in the first‐order dorsal root ganglia neurons ( 1 Chang et al., 2017, 2 Sun et al., 2018, 3 Blesneac et al., 2018, 4 Alsaloum et al., 2019, 5 Meents et al., 2019, 6 Qu et al., 2019, 7 Duggett et al., 2017, 8 Yan et al., 2013, 9 McGuinness et al., 2010, 10 Hasbargen et al., 2010, 11 Tan et al., 2020, 12 Luo et al., 2001, 13 Newton et al., 2001, 14 Tachiya et al., 2018, 15 Boroujerdi et al., 2008, 16 Nguyen et al., 2009, 17 Zhou & Luo, 2014).…”
Section: Pathogenic Mechanisms and Recent Findingsmentioning
confidence: 99%
“…Besides Na V 1.7, special focus was laid on Na V 1.8, and Na V 1.9. Following injury or chemotherapy, secretion of signal molecules may upregulate the expression of Na V 1.7 in rats and humans, and cause an enhanced excitability (Chang et al., 2017; Sun et al., 2018). Other findings suggest that de novo expression of Na V 1.8 is reduced in patients after peripheral nerve injury, while already present channels accumulate at the injury sites (Coward et al., 2000).…”
Section: Pathogenic Mechanisms and Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that dorsal root ganglion (dRG) neurons are closely associated with neuropathic pain. changes in neurotrophic factors, inflammatory factors and expression Upregulation of Na v 1.7 by endogenous hydrogen sulfide contributes to maintenance of neuropathic pain JUN-JIE TIAN 1,2* , cHAO-YANG TAN 1,3* , QIN-YI cHEN 1,4* , YING ZHOU 1,5 , ZU-WEI QU 6 , MENG ZHANG 7,8 , KE-TAO MA 1,9 , WEN-YAN SHI 1,9 , LI LI 10 and JUN-QIANG SI 1,9,11 of various ion channels in dRG neurons result in increased excitability of dRG neurons, which underlie the development of neuropathic pain (3)(4)(5)(6)(7). Voltage-gated sodium channels (VGScs or Na v s) have been classified into nine different subtypes (Na v 1.1-1.9), seven of which are expressed on human dRG neurons (Na v 1.1-1.3 and Na v 1.6-1.9).…”
Section: Introductionmentioning
confidence: 99%